Dukungan Sosial Teman Sebaya dan Persepsi Siswa Terhadap Cara Mengajar Guru dengan Motivasi Belajar - Muhamad Uyun (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Through the educational formal, students are expected to experience changing positive vibes. Nevertheless, many factors appeared in the process of learning. One of them is learning motivation. Following the researcher, salient factors are peer social support and students’ perceptions of teachers’ pedagogic with learning motivation. For that, the research interested to do the research. The study aimed to investigate the correlation between peer social support and students’ perception of teachers’ pedagogic with learning motivation. The statistical technique to test a hypothesis with multiple regression. The result of the analysis is proven that there was a positive correlation between peer social support and students’ perceptions on teachers’ pedagogic with learning motivation which showed that value = .497; p= 0,000. There was a significant positive relationship between peer social support with learning motivation (r=0.527; F=57.66; p<0,01), and there was a positive significance between students’ perceptions of teacher’s pedagogic with learning motivation (r=0,469; F=36,639; p=0,000 or p<0,01), with the effective contribution independent variable peer social support and students’ perceptions on teacher’s pedagogic with learning motivation of 27.8%. The conclusion of this research showed that there was a positive correlation between peer social support and students’ perceptions of teachers' pedagogic with learning motivation. There was a positive correlation between peer social support and students’ perceptions of teacher’s pedagogic with the learning motivation, and there was a positive significance between students’ perceptions of teacher’s pedagogic with learning motivation.Keywords: Peer Social Support, Students’ perceptions on teacher’s pedagogic, Learning motivation. Melalui pendidikan formal, peserta didik diharapkan mengalami perubahan yang lebih positif. Namun demikian, akan ada banyak faktor yang muncul dalam proses pembelajaran. Salah satunya yaitu motivasi belajar. Menurut peneliti faktor yang dominan adalah dukungan sosial teman sebaya dan persepsi siswa terhadap cara mengajar guru. Untuk itulah peneliti tertarik untuk membuktikannya lebih lanjut. Tujuan penelitian ini untuk mengetahui ada korelasi dukungan sosial teman sebaya dan persepsi siswa terhadap cara mengajar guru dengan motivasi belajar. Teknik statistik untuk menguji hipotesis dengan mengunakan regresi ganda. Hasil analisis data terbukti bahwa ada hubungan positif yang signifikan antara dukungan sosial teman sebaya dan persepsi siswa terhadap cara mengajar guru dengan motivasi belajar yang ditunjukkan oleh nilai r= 0.497; p= 0,000. Ada hubungan positif yang signifikan antara dukungan sosial teman sebaya dengan motivasi belajar (r=0.527; F=57.66; p<0,01), dan ada hubungan positif yang signifikan antara persepsi siswa terhadap cara mengajar guru dengan motivasi belajar (r=0,469; F=36,639; p=0,000 atau p<0,01), dengan sumbangan efektif variabel bebas dukungan sosial teman sebaya dan persepsi siswa terhadap cara mengajar guru sebesar 27,8%. Adapun kesimpulan penelitian Ada hubungan positif yang signifikan antara dukungan sosial teman sebaya dan persepsi siswa terhadap cara mengajar guru dengan motivasi belajar. Ada hubungan positif yang signifikan antara dukungan sosial teman sebaya dengan motivasi belajar, dan ada hubungan positif yang signifikan antara persepsi siswa terhadap cara mengajar guru dengan motivasi belajar.Kata Kunci: Dukungan Sosial Teman Sebaya, Persepsi Siswa terhadap Cara Mengajar Guru, Motivasi Belajar